Hematological Profile of Indigenous Kangayam Calves in Relation to Age and Sex - Karumalaisamy, Devipriya; Palanisamy, Selvaraj; Santhanam, Jayachandran; K, Balasundaram; K, Sivakumar; Sakthivelu, Manokaran (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The objective of the study was to establish the reference range of hematological parameters for indigenous Kangayam calves of Tamil Nadu, India. The indigenous male and female Kangayam calves from birth to one year of age of both sex were selected for this study (n = 10). Blood samples were collected at 3, 6, 9, and 12 months of age. The hematological parameters were estimated by an automated blood cell analyzer, and the morphometry of red blood cells was studied using an ocular micrometer in a microscope. The overall value (Mean ±SE) of hemoglobin (Hb), packed cell volume (PCV), red blood cell (RBC), white blood cell (WBC), lymphocytes, monocytes, neutrophils, basophils, eosinophils, and platelet were recorded. Hb, PCV, and RBC values showed a highly significant (p ≤0.01) difference in female Kangayam calves among different age groups among all hematological parameters. A significant (p ≤0.05) decrease was recorded in WBC with advancement of age in Kangayam male calves. No significant difference was noticed in platelets and basophils in both sexes up to one-year age. Other parameters like lymphocyte, monocytes, neutrophils, eosinophils, MCV, MCH, and MCHC showed highly significant (p ≤0.01) differences among the different age groups of both sexes. There is no significant difference in RBC size among the different age groups in both the sexes. The estimated hematological profile of Kangayam calves will serve as baseline values to the clinician during different clinical conditions.